A system-wide approach to explaining variation in potentially avoidable emergency admissions: national ecological study. Issue 1 (31st July 2013) - O'Cathain, Alicia; Knowles, Emma; Maheswaran, Ravi; Pearson, Tim; Turner, Janette; Hirst, Enid; Goodacre, Steve; Nicholl, Jon
Abstract : Background: Some emergency admissions can be avoided if acute exacerbations of health problems are managed by the range of health services providing emergency and urgent care. Aim: To identify system-wide factors explaining variation in age sex adjusted admission rates for conditions rich in avoidable admissions. Design: National ecological study. Setting: 152 emergency and urgent care systems in England. Methods: Hospital Episode Statistics data on emergency admissions were used to calculate an age sex adjusted admission rate for conditions rich in avoidable admissions for each emergency and urgent care system in England for 2008–2011. Results: There were 3 273 395 relevant admissions in 2008–2011, accounting for 22% of all emergency admissions. The mean age sex adjusted admission rate was 2258 per year per 100 000 population, with a 3.4-fold variation between systems (1268 and 4359). Factors beyond the control of health services explained the majority of variation: unemployment rates explained 72%, with urban/rural status explaining further variation (R 2 =75%). Factors related to emergency departments, hospitals, emergency ambulance services and general practice explained further variation (R 2 =85%): the attendance rate at emergency departments, percentage of emergency department attendances converted to admissions, percentage of emergency admissions staying less than a day, percentage of emergency ambulance calls not transported to hospital and perceived access to general practice within 48 h. Conclusions: Interventions to reduce avoidable admissions should be targeted at deprived communities. Better use of emergency departments, ambulance services and primary care could further reduce avoidable emergency admissions.